PENGEMBANGAN MODEL PEMBERDAYAAN BAGI PENGOLAH IKAN GUNA MENINGKATKAN PENDAPATAN (Studi Kasus Pada Pengolah Ikan Di Kabupaten Cilacap) - Ida Ayu Kade Rachmawati Kusasih, Christiawan Hendratmoko Budi Istiyanto (PARADIGMA, 2015)
The aims of this research are to analyze the power of fish-processor,Â evaluated by economic and non economic aspect, to analyze the performance of Â ishprocessingÂ by R/C ratio, to analyze the role of stakeholders in increasing fishprocessorâsÂ income, and to formulate the strategy of empowerment for fishprocessor.Â Primary data populated from 109 respondents in South Cilacap Subdistrict.The analysis methods used are descriptive statistics, crosstab analysis, andanalytical of process hierarchy.Â The results of study indicate that the powers of fish-processor are still less,Â they have low level income with R/C ratio 1,03 up to 1,67. The roles of stakeholdersÂ toward coastal area community are still poor. Therefore, we need strategy toÂ empower them by giving loan (credit), reviving the fish-processorâs organization,Â and giving information and training about modern technical of fish-processing.Keywords: the power of fish- processor; stakeholders; R/C ratio